2021
DOI: 10.1007/s12325-021-01989-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sodium-Glucose Cotransporter-2 Inhibitors in Clinical Practice for Heart Failure Prevention and Treatment: Beyond Type 2 Diabetes. A Narrative Review

Abstract: Despite the availability of established treatments, heart failure (HF) is associated with a poor prognosis and its management is suboptimal, highlighting the need for new options for treatment and prevention. Patients with type 2 diabetes (T2D) often experience cardiovascular (CV) complications, with HF being one of the most frequent. Consequently, several CV outcome trials have focused on glucose-lowering therapies and their impact on CV outcomes. An established treatment for T2D, sodium-glucose cotransporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 76 publications
(158 reference statements)
0
14
0
Order By: Relevance
“…Empagliflozin is an inhibitor of sodium-glucose cotransporter-2 and thus used as an anti-diabetic drug to treat adult patients with type-2 diabetes [ 38 ]. It was also reported to help prevent heart failure [ 39 ]. Adult cardiomyocytes were incubated with high glucose or mannitol (25 mmol/L) in the presence of empagliflozin (1 µmol/L, Cedarlane, Burlington, Ontario, Canada) [ 40 ] or vehicle for 24 h. Co-incubation with empagliflozin significantly reduced high glucose-induced levels of phosphorylated RIPK3 and MLKL in cardiomyocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Empagliflozin is an inhibitor of sodium-glucose cotransporter-2 and thus used as an anti-diabetic drug to treat adult patients with type-2 diabetes [ 38 ]. It was also reported to help prevent heart failure [ 39 ]. Adult cardiomyocytes were incubated with high glucose or mannitol (25 mmol/L) in the presence of empagliflozin (1 µmol/L, Cedarlane, Burlington, Ontario, Canada) [ 40 ] or vehicle for 24 h. Co-incubation with empagliflozin significantly reduced high glucose-induced levels of phosphorylated RIPK3 and MLKL in cardiomyocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The medication also showed the same efficacy and adverse event profile in the Asian population compared to the non-Asian population [9]. Empagliflozin is currently recommended as pharmacological therapy for HFrEF patients by the FDA, 2021 ESC guidelines, and 2021 guidelines of the Japanese Circulation Society and Japanese Heart Failure Society (JCS/JHFS) [3,4,10]. The risk of cardiorenal outcomes was reduced after treatment with empagliflozin in addition to other HF therapy in HFrEF patients both with and without DM.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have suggested its effectiveness in patients with heart failure with preserved ejection fraction (HFpEF) [2]. The drug was also recently approved by the U.S. Food and Drug Administration (FDA) and recommended in the 2021 European Society of Cardiology (ESC) guidelines for use in heart failure with reduced ejection fraction (HFrEF) [3,4]. In addition, trials have shown that SGLT-2 inhibitors are effective in reducing the risk of myocardial infarction (MI), stroke, and primary outcomes of chronic kidney disease (CKD) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the general population the levels of NPs were inversely associated with incident T2DM and its progression, but their concentrations remained high in prognostic accuracy for all-causes death and hospitalization due to HF [ 40 , 41 ]. However, SGLT2 inhibitors reduced a number of serious HF events and improved clinical status in HF patients regardless of volume overload and consequently independently from the baseline level [ 42 , 43 , 44 ], pool of electrolytes and metabolic profile [ 45 , 46 ]. Overall, the cardiac protective effects of SGLT-2 inhibitors in patients with T2DM and HF are most likely attributable to multiple mechanisms, including peroxisome proliferator-activated receptor gamma- and perilipin-related metabolic effects, sirtuin-dependent anti-inflammatory and tissue protective effects, MAPK kinase/ERK dependent inhibition on adipogenesis and lipolysis [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%